Peluang Ekspansi Energi Terbarukan Biomassa dengan Analisis SWOT - Juwita Juwita; Syaifuddin Yana; Maksalmina Maksalmina; Mahdi Mahdi; Fitriliana Fitriliana; Filia Hanum; Kasmaniar Kasmaniar (Jurnal Serambi Engineering, 2023)
Fossil energy demand rises with global population. Rising consumption has depleted non-renewable energy sources. Thus, many governments are seeking new renewable energy sources (EBT). Biomass has great promise as renewable energy. This study examines Indonesia’s biomass energy potential. Indonesia’s new and renewable energy capacity will be 49.81 GW (gigawatts). But only 445 Megawatts are deployed (MW). However, opposing interests and conflicts persist in its application. EBT development need a solution to this problem. SWOT was used to find answers for these issues. The draft strategies optimize coordination and collaboration between intersecting subsectors (agriculture, plantations, and forestry) from ministries and industries (food, chemicals, animal feed, cosmetics and others). Optimizing regulations to manage competing interests across major companies including food, chemical, cosmetics, and energy and between sectors, especially to meet renewable energy demands. However, government cooperation and regulation must be strengthened to optimize research and development for alternative renewable energy.